Obesity, metabolic dysregulation, and cancer: a growing concern and an inflammatory (and microenvironmental) issue - Hursting, Stephen D.; Dunlap, Sarah M. (Annals of the New York Academy of Sciences, 2012)
Obesity is an established risk and progression factor for many cancers. In the United States more than one‐third of adults, and nearly one in five children, are currently obese. Thus, a better understanding of the mechanistic links between obesity and cancer is urgently needed to identify intervention targets and strategies to offset the procancer effects of obesity. This review synthesizes the evidence on key biological mechanisms underlying the obesity–cancer association, with particular emphasis on obesity‐associated enhancements in growth factor signaling, inflammation, and perturbations in the tumor microenvironment. These interrelated pathways and processes represent mechanistic targets for disrupting the obesity–cancer link.